Thrombosis of the lower right limb in an 11-year-old boy - the first manifestation of systemic lupus erythematosus triggered by SARS-CoV-2 infection - Karolina Frąckowiak; Jacek Zachwieja; Katarzyna Jończyk; Andrzej Blumczyński; Danuta Ostalska-Nowicka (Termedia Publishing House, 2024)
The case report describes an 11-year old boy with sudden onset lower right limb thrombosis, hypertension and nephritic syndrome. Laboratory findings revealed positive results of anti-ANA, anti-dsDNA, lupus anticoagulant and COVID-19 IgG antibodies. Vascular ultrasound and computed tomography detected active thrombosis of the right popliteal vein. Kidney biopsy confirmed fourth class lupus nephritis. The patient responded well to a combination of steroids, cyclophosphamide, hydroxychloroquine, rituximab, alteplase, heparin and amlodipine, with the resolution of thrombosis and nephritic syndrome, stabilization of blood pressure and improvement in laboratory findings. The case highlights the importance of prompt diagnosis and appropriate treatment of systematic lupus erythematosus with vein thrombosis and lupus nephritis in children, particularly in male patients. Overall, this case emphasizes the possibility of virus triggering factors in systematic lupus erythematosus and the importance of regular check-ups, monitoring of symptoms in preventing complications and improving the long-term outlook for patients with systemic lupus erythematosus.